Caretas e máscaras: design em correspondências com os materiais no artesanato da Costa Rica e do Maranhão - ALPÍZAR, Gloriana Solís (2020)
In this research we discuss the use of materials as an essential part in the practice of the Design, being the way the designers transmit their ideas from the intangible world to the tangible world of production. We try to answer the question: what we can learn with the creative process of masks and grimaces craftsmen, between the Borucas from Costa Rica and a master of Cazumba grimaces from Maranhão, Brazil, about the qualitative use of the material in the Design? It's also discussed the participation and the flow of the materials in a physical and symbolic way in the society. Besides that, through correspondence relations, the encounter of designers and craftsmen between Maranhão e Costa Rica, through the theme of making masks and grimaces as well as the creative process that involves them. Through different theories and analysis the interference of creativity, imagination and intuition and the constant contact with the materials is exposed. The same way we show the variants that can bring social, historical and cultural aspects. Like this, the present research emerges as a link to guide us through the collaborative process of the Design as per the Design Anthropology. We took in consideration the craftsmen as co-researchers of this investigation, and presenting them as a fundamental part of this work. The experience in the field is a result of sharing directly with the five craftsmen, through participant observation and the correspondence relations with them and the environment. Thus, the resulting analysis is part of a triangulation between the theories researched, the experiences of the researchers in the field and the knowledge of the co researchers, in order to make this analysis tangible, graphics were developed to illustrate it. Once the objectives are met, there is a proposal for reflection on what happens in the daily practices of us as designers, in addition to examples resulting from how the work through correspondence had organic responses to the logo of this research.